Implementation of the Breadth First Search Algorithm in the Darkness Maze Game Based on Desktop Intelligent Agent - Ramadhani Suciansyah; Bartholomius Harpad; Hanifah Ekawati (Politeknik Pertanian Negeri Samarinda, 2021)
This research was developed with a multimedia development stage consisting of 6 stages, namely Concept, Design, Material Collecting, Assembly, Testing and Distribution. Analysis of system design using UML (Unified Modeling Language) which consists of Use Case Diagrams, Activity Diagrams and Sequence Diagrams. In the development of this 3D game using the Unity Engine as software designed for the creation and development of video games assisted by typing some coding programs. The test method uses Black-Box testing and Beta Testing. Testing and Distribution (Distribution). Analysis of system design using UML (Unified Modeling Language) which consists of Use Case Diagrams, Activity Diagrams and Sequence Diagrams. In developing this 3D game using the Unity Engine as software designed for the creation and development of video games assisted by typing some coding programs. The test method uses Black-Box testing and Beta Testing. Testing and Distribution . Analysis of system design using UML (Unified Modeling Language) which consists of Use Case Diagrams, Activity Diagrams and Sequence Diagrams. In developing this 3D game using the Unity Engine as software designed for the creation and development of video games assisted by typing some coding programs. The test method uses Black-Box testing and Beta Testing. The final results of this study can be applied with the help of typing coding so that the path points that have been created can provide information about adjacent paths so that they can find an exit path.